ChemInform Abstract: Formal [4 + 2] Reaction Between 1, 3‐Diynes and Pyrroles: Gold(I)‐Catalyzed Indole Synthesis by Double Hydroarylation. Issue 24 (June 2015) - Matsuda, Yuka; Naoe, Saori; Oishi, Shinya; Fujii, Nobutaka; Ohno, Hiroaki
Abstract: The novel protocol combines a hydroarylation of 1, 3‐diynes with pyrroles with a subsequent intramolecular hydroarylation to furnish 4, 7‐disubstituted indoles under mild conditions.